Design of multiple microcontrollers platform for use in academic environment - Selvakumar, Raja Saravana Kumar (2012)
Embedded systems have an everyday presence and direct impact in every day’s lives. Therefore, learning institutions are continuously improving their courses in microcontroller and embedded system programming. Although the diversity of curriculums, the availability of learning tools, where the student can practice and improve their skills, is a key factor to the success of the learning process. The platform developed and presented in this thesis results from author’s experience in teaching and learning embedded systems. From the analysis of teaching and learning needs, a learning environment based on the Freescale HC11, MCS51, and Microchip PIC 18 Series families was designed, which led to the Multiple Microcontrollers Evaluation Tool (MicroEVAT). This tool can be expanded by modules and adjusted at a specific time to student's real needs. All modules can be interconnected by an IDE bus, allowing expanding the capabilities of the platform. Series of test-run are conducted to verify MicroEVAT system performance. The developed modules allow the practice of subjects related with digital Input and Output interface, analogue interface, user interface, wireless communications, and energy management and conservation. The hardware, software and system architecture used to develop the MicroEVAT are described in detailed in this thesis. In this respect, the MicroEVAT were applicable for education and expose the electrical engineering students to the understanding of microcontroller in electronic design field and embedded systems. The work done for this research project gives solid bases and chances for fast evolution in embedded control technology research.